Supernatural. Season fourteen [videorecording (DVD)] - Padalecki, Jared, 1982-; Ackles, Jensen; Collins, Misha; Beaver, Jim, 1950- (Warner Bros. Entertainment, 2019)
In season thirteen, the Winchester brothers were thrown into a frightening alternative universe, an apocalyptic domain where they were never born, all while training Jack and saving their mother. And they won. But with Lucifer's apparent death came a new obstacle to face in season fourteen, the Archangel Michael, who has now escaped the other universe in Dean's body! Sam, Castiel, and Jack are working on getting Dean back and stopping Michael before his Apocalypse-World agenda gains strength.